2019
DOI: 10.3389/fphar.2019.01350
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitor-Associated Cardiotoxicity: Current Understanding on Its Mechanism, Diagnosis and Management

Abstract: Immune checkpoint inhibitors (ICIs) that target cytotoxic T lymphocyte antigen 4, programmed cell death-1, and PD-ligand 1 have revolutionized cancer treatment, achieving unprecedented efficacy in multiple malignancies. ICIs are increasingly being used in early cancer settings and in combination with various other types of therapies, including targeted therapy, radiotherapy, and chemotherapy. However, despite the excellent therapeutic effect of ICIs, these medications typically result in a broad spectrum of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 141 publications
(319 reference statements)
1
71
3
1
Order By: Relevance
“…However, ICIs showed several autoimmune or inflammatory side effects, collectively termed immune-related adverse events, including diabetes, chronic inflammatory bowel diseases, thyroiditis and cardiovascular diseases [ 6 ]. Cardiovascular immune-related adverse events involved myocarditis [ 7 ]; its pathogenesis is based on lymphocytic infiltration in myocardial tissue and a direct/indirect interaction with cardiomyocytes expressing PD-1/PDL-1 and other immune-sensitive antigens [ 7 , 8 ]. The prevalence of myocarditis ranged from 0.06% to 2.4%, with a higher risk in combination immunotherapy [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, ICIs showed several autoimmune or inflammatory side effects, collectively termed immune-related adverse events, including diabetes, chronic inflammatory bowel diseases, thyroiditis and cardiovascular diseases [ 6 ]. Cardiovascular immune-related adverse events involved myocarditis [ 7 ]; its pathogenesis is based on lymphocytic infiltration in myocardial tissue and a direct/indirect interaction with cardiomyocytes expressing PD-1/PDL-1 and other immune-sensitive antigens [ 7 , 8 ]. The prevalence of myocarditis ranged from 0.06% to 2.4%, with a higher risk in combination immunotherapy [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that severity of vascular calcification by qualitative assessment of non-gated CT imaging was associated with the occurrence of CV events in ICI therapy. Though the exact pathophysiology of CV events on ICI therapy remains unclear, direct and indirect immune-mediated inflammation are possible mechanisms that may be compounded by underlying atherosclerosis [17]. ICI therapies augment T-cell responses, leading to increased cytotoxic CD8+ T-cell activity, decreased regulatory T-cell activity, and increased production of inflammatory cytokines including IL-2, IL-6, IL-17, TNFα, and IFNγ [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Endomyocardial biopsy has been suggested as the gold standard diagnostic method in ICI-related myocarditis ( 17 , 30 , 31 ). Detection of lymphocytic infiltration along with myocyte necrosis in the biopsy material is of diagnostic value.…”
Section: Introductionmentioning
confidence: 99%
“…Although no strong evidence-based recommendations has been reported, suppression of high-grade inflammatory response within the myocardium largely through immunosuppressive agents has been suggested as a milestone in the treatment of ICI-associated myocarditis ( 24 , 30 , 33 , 34 ). Within this context, even though corticosteroids ( 7 ) appear to be the basis of immunosuppressive therapy, cases have been reported where treatment regimens including antithymocyte globulin ( 6 ), mycophenolate mofetil ( 6 ), abatacept ( 33 ), alemtuzumab ( 34 ), tacrolimus ( 30 ), and rituximab ( 30 ) have been initiated depending on LVEF, hs-troponin level along with hemodynamic status. The common mechanism of action of these agents is to induce the inactivation or destruction of T cells, that are considered to play a pivotal role in the evolution of myocarditis, as confirmed by endomyocardial biopsy findings of patients with ICI-related myocarditis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation